2016
DOI: 10.18410/jebmh/2016/1176
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Lesions of Uterine Cervix

Abstract: BACKGROUND Uterine cervix acts as a "gateway" for various infections, which affects cervix, uterus and upper genital tract, thus working under various pathological conditions leading to various lesions of cervix as well as acting as a sentinel for upper genital tract infections. Cervical specimens like biopsies and sections of cervix from hysterectomy specimens form a significant part of surgical specimens in any histopathology laboratory. Among all cervical lesions, cervical inflammatory lesions are the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sidhalingreddy et al and Sneha Sainy et al also found endocervical polyps as the most common type of polypoidal lesion followed by leiomyomatous polyps and fibroepithelial polyps. 22,23 Nelson LA et al also found endocervical polyps (57.1%) as the most common followed by inflamed endocervical polyps (21%) and next most frequent-endometrial polyp (6.2%). 24 In our study there were no malignancy or dysplasia reported in the cervical polyps .Senturk MB et al Mackenzie I et al and Tirlapur SA et al also found no features of atypia, dysplasia or malignancy.…”
Section: Discussionmentioning
confidence: 92%
“…Sidhalingreddy et al and Sneha Sainy et al also found endocervical polyps as the most common type of polypoidal lesion followed by leiomyomatous polyps and fibroepithelial polyps. 22,23 Nelson LA et al also found endocervical polyps (57.1%) as the most common followed by inflamed endocervical polyps (21%) and next most frequent-endometrial polyp (6.2%). 24 In our study there were no malignancy or dysplasia reported in the cervical polyps .Senturk MB et al Mackenzie I et al and Tirlapur SA et al also found no features of atypia, dysplasia or malignancy.…”
Section: Discussionmentioning
confidence: 92%
“…The "transformation zone" that is where squamous and columnar meets predispose to highly susceptible infections with HPV and neoplasms [2]. Thus, this acts as a "gateway" for various infections, cervical precursor lesions, which affects the cervix [3]. The cervical lesions are characterized as nonneoplastic, preinvasive and invasive neoplastic lesions [4].…”
Section: Introductionmentioning
confidence: 99%
“…3 Uterine cervix acts as a "gateway" of various infections, which affects cervix, uterus and upper genital tract, thus working under various pathological conditions leading to various lesions of cervix as well as a sentinel for upper genital tract infections. 4 Hysterectomy is the most common major Gynaecological procedure in the world. It can be done through either abdominal or vaginal route.…”
Section: Introductionmentioning
confidence: 99%